Bibliometric visualization analysis of 'World Heritage' topic in web of science database using citespace - Wang, Suhua; Mohd Isa, Norliza; Li, Lintong; Shi, Keyi (Malque Publishing, 2024)
On November 22-23, 2023, UNESCO will convene its 24th session of the General Assembly of States Parties in Paris. In light of this, to ensure the ongoing dynamism and adaptability of knowledge pursuits in the realm of world heritage, this paper conducts a quantitative analysis of world heritage documents within the Web of Science (WOS) database. Leveraging CiteSpace 6.1.R6 software, we visually examine 5,208 documents with the topic "World Heritage" retrieved from 1979 to 2023. The research outcomes reveal the following key insights: (1) The literature in the field of world heritage research demonstrates a steadily increasing trend, with notable explosive growth starting in 2009 and reaching its peak in 2019. (2) Examination of collaborations with prominent authors, affiliated institutions, and contributing countries highlights the absolute superiority of the United States and Australia in the world heritage domain, attributed to their rich heritage and robust academic systems. Despite China ranking second in document publications, there is a need for increased international collaboration. (3) The most influential keywords include "Community", "The Great Barrier Reef" and "Managing World Heritage". (4) Heritage tourism, encompassing satisfaction, motivation, loyalty, and place attachment, emerges as the largest keyword cluster in the field of world heritage. (5) Recent research trends and hotspots include "Risk", "Building", "Intention", "Support", and "Stone". The research results provide a more comprehensive and systematic overview perspective for the world heritage field, which fills the gap and promotes the knowledge pursuit in the world heritage field.